كینث برنارد ومسرح التفاھة والھزل: صورة مصغرة لعالم مفكّك ومنھار - الدكتورة منى العلوان (College of Education for Women, 2019)
The paper deals with the contemporary American playwright, Kenneth Bernard, and his Theatre of the Ridiculous. This theatre, which originated in the 1960s and 1970s, aims at undermining dramatic and social conventions, and political, psychological, sexual, and cultural categories. It makes use of mass culture entertainment in America (television, popular songs, old movies, the circus) in its attempt to make us recognize the world as "ridiculous," a world which is both brutal and farcically trivial and insignificant, a world of ruthless powers, of freaks, clowns, and victims, of hysteria and absence of truth, a world, as Bernard describes it, "without hope, mercy, history, or any saving sociology or ideology." The paper is meant to shed light on the development of this theatre, its vision of and radical attitudes towards the world we live in (as illustrated in the plays of Bernard), and the postmodernist influences which went into its making.